Non-blending type HfB2 ceramic precursor, ceramic powder and preparation method

By selecting and controlling the types of hafnium, carbon and boron sources in the preparation of HfB2 ceramic powder, and combining prepolymerization and deep curing technologies, the problem of difficult atomic uniform mixing is solved, and the boron element loss problem is overcome. Preparation of high-purity ultrafine HfB2 ceramic powder.

CN119430951APending Publication Date: 2025-02-14INST OF CHEM CHINESE ACAD OF SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411576778.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the preparation of HfB2 ceramic powder is difficult to achieve atomic uniform mixing, which leads to the inability to completely react in some raw materials and remains in the product to become impurities, affecting the stability and use performance of the ceramic powder.

Method used

By selecting and controlling the types of hafnium sources, carbon sources and boron sources, and combining prepolymerization and deep curing, the deep curing products of HfB2 ceramic precursors that form chemical bonds between hafnium sources, boron sources and carbon sources are prepared, and the common The problem that the mixed boron source is prone to form a low boiling point boron oxide intermediate product during the cracking process.

Benefits of technology

The uniform distribution of Hf, B, C and O elements on the nanoscale is achieved, and the loss of boron elements is avoided, and high-purity ultra-fine HfB2 ceramic powder is obtained, which improves the crystal phase purity and use performance of the ceramic powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430951A_ABST
    Figure CN119430951A_ABST
Patent Text Reader

Abstract

The invention discloses a non-blending type HfB2 ceramic precursor, ceramic powder and a preparation method, the precursor adopts hafnium oxide as a hafnium source, boric acid ester as a boron source and phenolic resin as a carbon source, and the precursor comprises a cross-linked network formed by connecting the hafnium source, the boron source and the carbon source through chemical bonds; and the Hf, B, C and O elements in the precursor are uniformly distributed on the nanoscale. According to the precursor disclosed by the invention, low-boiling-point boron oxide is prevented from being easily formed in the cracking process of the blended boron source, so that the boron element is not easy to lose in the subsequent cracking process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of ultra-high temperature ceramic materials, and in particular, relates to a non-blended HfB2 ceramic precursor and ceramic powder and a preparation method thereof. Background Art

[0002] HfB2 ceramics have excellent high temperature resistance and ablation resistance, and play an important role in thermal protection materials for extreme aerospace environments. The preparation of high-quality HfB2 ceramic products requires high-quality HfB2 ceramic powder. However, the domestic production capacity of HfB2 ceramic powder is relatively weak, and only a few companies can produce in batches, but the quality is still far behind that of foreign products. The reason is related to many factors such as preparation route selection, process control level, and evaluation characterization.

[0003] High-quality HfB2 ceramic powders in the prior art are generally prepared by the precursor sol-gel process, but there is a problem that the raw materials cannot be mixed uniformly at the atomic level, resulting in the inability of some raw materials to react completely and remaining in the product as impurities, thereby affecting the stability and performance of the HfB2 ceramic powder during molding and use. For example, in the cracking and transformation process from organic to inorganic, the first thing formed by the cracking of the precursor is an oxide intermediate, and the primary oxide grains are highly active and easily grow in size, which in turn causes the cracking products to separate into phases, affecting the uniformity of element distribution and the activity of carbon thermal reduction reactions at higher temperatures. For example, patent CN201911239788.0 uses a vacuum cracking process to reduce the starting temperature of the carbon thermal reduction reaction between zirconium oxide and carbon to the same temperature range as the initial formation temperature of the zirconium oxide intermediate crystal phase (≤850°C), thereby utilizing the newly formed carbide crystal phase to inhibit the further growth of the zirconium oxide grain size, thereby reducing the uneven distribution of elements, improving the activity of the carbon thermal reduction reaction, and finally obtaining a high-purity ultrafine zirconium carbide ceramic powder. However, there has been no report on the preparation of HfB2 ceramic powder by vacuum atmosphere pyrolysis. The reason is that the HfB2 ceramic precursor is prone to boron loss when pyrolyzed in a normal pressure atmosphere. If a vacuum pyrolysis process is further adopted, the loss of boron will be more serious, which will affect the crystal purity of the HfB2 ceramic powder. The specific process is: Boric acid is often used as a boron source in the sol-gel route. Boron oxide is first formed during the pyrolysis conversion process. The melting point of boron oxide is relatively low, only 450°C. In the carbon thermal reduction reaction temperature range of 1200°C, boron oxide evaporates rapidly and uncontrollably, thus affecting the boron content of the ceramic product. If a vacuum process is used for pyrolysis, this problem will undoubtedly be aggravated. The root cause of the above problems is that in the gel network of the HfB2 ceramic precursor, the boron source exists in a free state and does not form a chemical connection with the zirconium source and the carbon source. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the present invention provides a non-blended HfB2 ceramic precursor and powder. In the process of preparing the precursor, the types of hafnium source, carbon source and boron source are selected and controlled, and combined with prepolymerization and deep curing, a deeply cured HfB2 ceramic precursor product in which the hafnium source, boron source and carbon source are chemically bonded is prepared. The problem that the blended boron source is prone to form a low-boiling point boron oxide intermediate during the cracking process, and the boron oxide is highly volatile and uncontrollable, is overcome; the non-blended HfB2 ceramic precursor of the present invention can meet the requirements of the vacuum atmosphere cracking process and be directionally converted into a high-purity ultrafine HfB2 ceramic powder.

[0005] Based on this, the technical solution adopted by the present invention is as follows:

[0006] A HfB2 ceramic precursor, wherein the precursor uses polyhafnium oxane as a hafnium source, borate as a boron source, and phenolic resin as a carbon source, and the precursor contains a cross-linked network in which the hafnium source, the boron source, and the carbon source are connected by chemical bonds, and the Hf, B, C, and O elements in the precursor are uniformly distributed on a nanoscale.

[0007] According to an embodiment of the present invention, the hafnium source, boron source and carbon source are prepolymerized and heated to form a gel, and then deeply cured to obtain the precursor.

[0008] According to an embodiment of the present invention, the mass ratio of Hf element to borate ester and phenolic resin in polyhafnium oxide is 1:(3-15):(0.1-1), preferably 1:(3-10):(0.1-0.6).

[0009] According to an embodiment of the present invention, the boric acid ester is a reaction product of boric acid and at least one of polyols such as ethylene glycol, glycerol, pentaerythritol, xylitol, and sorbitol.

[0010] According to an embodiment of the present invention, the phenolic resin can be at least one of a variety of phenolic resins such as base-catalyzed phenolic resin, acid-catalyzed phenolic resin, allyl-modified phenolic resin, for example, the phenolic resin is at least one of barium phenolic resin, allyl-modified phenolic resin, and linear phenolic resin.

[0011] According to an embodiment of the present invention, the prepolymerization temperature is 70-120° C., for example, 70° C., 80° C., 90° C., 100° C. or 120° C., and the prepolymerization time is 2 h to 12 h.

[0012] According to an embodiment of the present invention, the heating temperature for forming the gel is 80-130°C, for example, 80°C, 90°C, 100°C, 120°C or 130°C; and the heating time is 7h-12h.

[0013] According to an embodiment of the present invention, the temperature of deep curing is 250-350°C, for example, 250°C, 260°C, 280°C, 300°C, 320°C or 350°C, and the time of deep curing is 4h-8h.

[0014] The present invention also provides a method for preparing the HfB2 ceramic precursor as described above, the method comprising:

[0015] (1) using polyhafnium oxane as a hafnium source, borate ester as a boron source, and phenolic resin as a carbon source, mixing the polyhafnium oxane, borate ester, and phenolic resin, and heating and prepolymerizing them in an inert atmosphere;

[0016] (2) The prepolymerized product is heated to form a gel, and the obtained gel is deeply cured in an air atmosphere to obtain the HfB2 ceramic precursor.

[0017] According to an embodiment of the present invention, in step (1), the prepolymerization temperature is 70 to 120° C., for example, 70° C., 80° C., 90° C., 100° C. or 120° C., and the prepolymerization time is 2 to 12 hours. Preferably, the prepolymerization is heated and stirred at the same time.

[0018] According to an embodiment of the present invention, in step (2), the heating temperature during the heating to form a gel is 80 to 130° C., for example, 80° C., 90° C., 100° C., 120° C. or 130° C., and the heating time is 7 to 12 hours. Preferably, stirring is not required during the heating to form a gel.

[0019] According to an embodiment of the present invention, in step (2), the temperature of deep curing is 250-350°C, for example, 250°C, 260°C, 280°C, 300°C, 320°C or 350°C, and the time of deep curing is 4h-8h.

[0020] The present invention also provides a HfB2 ceramic powder, which is a pyrolysis product of the HfB2 ceramic precursor in a vacuum atmosphere.

[0021] According to an embodiment of the present invention, the particle size of the HfB2 ceramic powder is 500nm to 5μm.

[0022] According to an embodiment of the present invention, the oxygen content in the HfB2 ceramic powder is 0.1% to 0.5%.

[0023] According to an embodiment of the present invention, the vacuum degree of the vacuum atmosphere pyrolysis is 300-650Pa.

[0024] According to an embodiment of the present invention, the cracking temperature is 1500-1650°C, for example, 1500°C, 1550°C, 1600°C or 1650°C, and the cracking time is 2h-6h.

[0025] The present invention also provides a method for preparing the HfB2 ceramic powder as described above, the method comprising: using the HfB2 ceramic precursor as described above, and subjecting it to vacuum cracking to obtain the HfB2 ceramic powder.

[0026] Beneficial effects of the present invention:

[0027] 1. The non-blended HfB2 ceramic precursor provided by the present invention comprises a cross-linked network in which the hafnium source, the boron source and the carbon source are chemically bonded, and the Hf, B, C and O elements in the precursor are uniformly distributed on a nanoscale. Such a precursor can avoid the formation of low-boiling boron oxide during the cracking process of the blended boron source, so that the boron element is not easily lost during the subsequent cracking process.

[0028] 2. In the preparation method of the non-blended HfB2 ceramic precursor provided by the present invention, the types of hafnium source, boron source and carbon source are screened, and pre-polymerized, heated to form a gel and deeply cured to obtain a non-blended HfB2 ceramic precursor cross-linked product in which the hafnium source, boron source and carbon source are chemically bonded to achieve atomic-level uniform dispersion of elements such as Hf, B, O, and C, thereby avoiding the formation of low-boiling boron oxide during the cracking process of the blended boron source, so that the boron element is not easily lost during the subsequent cracking process;

[0029] 3. In the HfB2 ceramic powder preparation method provided by the present invention, since the precursor realizes chemical solid boron, the problem of easy loss of boron element during the cracking process is overcome, and thus the method can be subjected to vacuum cracking process to obtain pure phase HfB2 ceramic powder. The method of the present invention has good universality, high controllability, and is easy to realize engineering stable preparation, which can solve the problem of stable batch preparation of domestic high-quality HfB2 ceramic powder.

[0030] 4. In the preparation method of HfB2 ceramic powder provided by the present invention, by controlling the atmosphere conditions of the cracking process, preferably the vacuum cracking process, the starting temperature of the carbon thermal reduction reaction is reduced to below 850°C, and the HfB2 ceramic phase formed at 850°C plays a role in inhibiting the growth of the hafnium oxide grain size, avoiding the problem of low carbon thermal reduction reaction activity of large hafnium oxide grains. Thus, high-purity ultrafine HfB2 ceramic powder is obtained at a relatively low temperature (≤1650°C), the average particle size of the powder is adjustable between 500nm and 5μm, and the oxygen content in the HfB2 ceramic powder is lower than 0.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a SEM image of the vacuum pyrolysis product of the HfB2 precursor in Example 1 after air curing at 1500°C;

[0032] Figure 2 is a SEM image of the vacuum pyrolysis product of the HfB2 precursor in Example 2 after air curing at 1500°C;

[0033] Figure 3 is a SEM image of the vacuum pyrolysis product of the HfB2 precursor in Example 3 after air curing at 1550°C;

[0034] Figure 4 This is a SEM image of the vacuum pyrolysis product of the HfB2 precursor in Example 4 after air curing at 1600°C.

[0035] Figure 5 This is the XRD diagram of the vacuum pyrolysis product of the HfB2 precursor in Example 1 after air curing at 1500°C. DETAILED DESCRIPTION

[0036] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0037] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0038] Example 1

[0039] In this embodiment, the non-blended HfB2 ceramic precursor is prepared by the following method:

[0040] Polyhafnium oxide, borate and phenolic resin are mixed evenly in a mass ratio of Hf element: borate: phenolic resin of 1:4:0.2, and then heated to 70°C in an argon atmosphere and prepolymerized for 60 minutes to obtain a non-blended HfB2 ceramic precursor; the borate is a condensation product of boric acid and propylene glycol, and the phenolic resin is a barium phenolic resin.

[0041] The above products were first heated at 90°C for 10 hours until all gels were formed, and then transferred to a rotary kiln after drying. The rotary kiln was passed through an air atmosphere and heated to 250°C for deep curing for 6 hours to obtain a cross-linked non-blended HfB2 ceramic precursor.

[0042] In this embodiment, the prepared non-blended HfB2 ceramic precursor is continued to be used to prepare HfB2 ceramic powder according to the following method:

[0043] The above products were placed in a graphite furnace, heated to 1500°C in a vacuum atmosphere and pyrolyzed for 3 hours to obtain HfB2 ceramic powder.

[0044] After testing, XRD results showed that the obtained HfB2 ceramic powder was pure phase HfB2, SEM results showed that the obtained HfB2 particles were distributed between 500nm and 5μm, with an average particle size of 3.5μm, and the nitrogen and oxygen analyzer test results showed that the oxygen content was 0.45%.

[0045] Example 2

[0046] In this embodiment, the non-blended HfB2 ceramic precursor is prepared by the following method:

[0047] Polyhafnium oxide, borate and phenolic resin are mixed evenly in a mass ratio of Hf element: borate: phenolic resin of 1:4:0.24, and then heated to 90°C in an argon atmosphere and prepolymerized for 60 minutes to obtain a non-blended HfB2 ceramic precursor; the borate is a condensation product of boric acid and glycerol, and the phenolic resin is an allyl-modified phenolic resin.

[0048] The above products were first heated at 120°C for 6 hours until all gels were obtained, and then transferred to a rotary kiln after drying. The rotary kiln was passed through an air atmosphere and heated to 300°C for deep curing for 2 hours to obtain a cross-linked non-blended HfB2 ceramic precursor.

[0049] In this embodiment, the prepared non-blended HfB2 ceramic precursor is continued to be used to prepare HfB2 ceramic powder according to the following method:

[0050] The above products were placed in a graphite furnace, heated to 1500°C in a vacuum atmosphere and pyrolyzed for 3 hours to obtain HfB2 ceramic powder.

[0051] After testing, XRD results showed that the obtained HfB2 ceramic powder was pure phase HfB2, SEM results showed that the obtained HfB2 particle size distribution was between 500nm and 5μm, with an average particle size of 3.2μm, and the nitrogen and oxygen analyzer test results showed that the oxygen content was 0.34%.

[0052] Example 3

[0053] In this embodiment, the non-blended HfB2 ceramic precursor is prepared by the following method:

[0054] Polyhafnium oxide, borate and phenolic resin are mixed evenly in a mass ratio of Hf element: borate: phenolic resin of 1:3:0.2, and then heated to 70°C in an argon atmosphere and prepolymerized for 60 minutes to obtain a non-blended HfB2 ceramic precursor; the borate is a condensation product of boric acid and sorbitol, and the phenolic resin is a barium phenolic resin.

[0055] The above products were heated at 80°C for 10 hours until all gelled, and then dried and transferred to a rotary kiln. The rotary kiln was passed through an air atmosphere and heated to 350°C for deep curing for 2 hours to obtain a cross-linked non-blended HfB2 ceramic precursor.

[0056] In this embodiment, the prepared non-blended HfB2 ceramic precursor is continued to be used to prepare HfB2 ceramic powder according to the following method:

[0057] The above products were placed in a graphite furnace, heated to 1550°C in a vacuum atmosphere for 3 hours to obtain HfB2 ceramic powder.

[0058] After testing, XRD results showed that the obtained HfB2 ceramic powder was pure phase HfB2, SEM results showed that the obtained HfB2 particle size was 500nm~2μm, the average particle size was 1.1μm, and the nitrogen and oxygen analyzer test results showed that the oxygen content was 0.29%.

[0059] Example 4

[0060] In this embodiment, the non-blended HfB2 ceramic precursor is prepared by the following method:

[0061] Polyhafnium oxide, borate and phenolic resin are mixed evenly in a mass ratio of Hf element: borate: phenolic resin of 1:4:0.2, and then heated to 120°C in an argon atmosphere and prepolymerized for 60 minutes to obtain a non-blended HfB2 ceramic precursor; the borate is a condensation product of boric acid and ethylene glycol, and the phenolic resin is a linear phenolic resin.

[0062] The above products were first heated at 120°C for 10 hours until all gels were formed, and then transferred to a rotary kiln after drying. The rotary kiln was passed through an air atmosphere and heated to 300°C for deep curing for 2 hours to obtain a cross-linked non-blended HfB2 ceramic precursor.

[0063] In this embodiment, the prepared non-blended HfB2 ceramic precursor is continued to be used to prepare HfB2 ceramic powder according to the following method:

[0064] The above products were placed in a graphite furnace, heated to 1600°C in a vacuum atmosphere and pyrolyzed for 2 hours to obtain HfB2 ceramic powder.

[0065] After testing, XRD results showed that the obtained HfB2 ceramic powder was pure phase HfB2, SEM results showed that the obtained HfB2 particle size was between 2μm and 7μm, with an average particle size of 4.6μm, and the nitrogen and oxygen analyzer test results showed that the oxygen content was 0.44%.

[0066] The above is an exemplary description of the embodiments of the present invention. However, the protection scope of the present invention is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A HfB2 ceramic precursor, characterized in that: The precursor uses polyhafnium oxane as a hafnium source, borate as a boron source, and phenolic resin as a carbon source. The precursor contains a cross-linked network in which the hafnium source, the boron source, and the carbon source are chemically bonded, and the Hf, B, C, and O elements in the precursor are uniformly distributed on a nanoscale.

2. The ceramic precursor according to claim 1, characterized in that The hafnium source, boron source and carbon source are prepolymerized and heated to form a gel, and then deeply cured to obtain the precursor. Preferably, the mass ratio of Hf element to borate ester and phenolic resin in polyhafnium oxide is 1:(3-15):(0.1-1).

3. The ceramic precursor according to claim 1 or 2, characterized in that: The borate ester is a reaction product of boric acid and at least one of ethylene glycol, glycerol, pentaerythritol, xylitol and sorbitol. Preferably, the phenolic resin is at least one of base-catalyzed phenolic, acid-catalyzed phenolic or allyl-modified phenolic, for example, the phenolic resin is at least one of barium phenolic resin, allyl-modified phenolic resin or linear phenolic resin.

4. The ceramic precursor according to any one of claims 1 to 3, characterized in that: The prepolymerization temperature is 70-120° C., and the prepolymerization time is 2 h to 12 h. Preferably, the heating temperature during the heating to form the gel is 80-130° C., and the heating time is 7 h to 12 h. Preferably, the deep curing temperature is 250-350° C., and the deep curing time is 4-8 hours.

5. The method for preparing a ceramic precursor according to any one of claims 1 to 4, characterized in that: The method comprises: (1) using polyhafnium oxane as a hafnium source, borate ester as a boron source, and phenolic resin as a carbon source, mixing the polyhafnium oxane, borate ester, and phenolic resin, and heating and prepolymerizing them in an inert atmosphere; (2) The prepolymerized product is heated to form a gel, and the obtained gel is deeply cured in an air atmosphere to obtain the HfB2 ceramic precursor.

6. A HfB2 ceramic powder, characterized in that: The ceramic powder is a pyrolysis product of the ceramic precursor according to any one of claims 1 to 4 in a vacuum atmosphere.

7. The powder according to claim 6, characterized in that The particle size of the HfB2 ceramic powder is 500nm-5μm. Preferably, the oxygen content in the HfB2 ceramic powder is 0.1% to 0.5%.

8. The powder according to claim 6, characterized in that The vacuum degree of the vacuum atmosphere cracking is 300-650Pa.

9. The powder according to claim 6, characterized in that: The cracking temperature is 1500-1650° C., and the cracking time is 2 h to 6 h.

10. A method for preparing the HfB2 ceramic powder according to any one of claims 6 to 9, characterized in that: The method comprises the following steps: using the HfB2 ceramic precursor and subjecting it to vacuum cracking to obtain HfB2 ceramic powder.

Citation Information

Patent Citations

  • Method for preparing hafnium boride powder by using boron / carbothermic method

    CN103754891A

  • Preparation method and application of boride ceramic precursor

    CN104086180A

  • C / SiC-HfB2 composite material and preparation method thereof

    CN110627514A

  • Preparation method of nano hafnium boride powder

    CN113816379A

  • Method for producing composite powder mb2-sic, where m = zr, hf

    RU2615692C1